Determinan Kinerja Instansi Pemerintah di Kabupaten Kebumen dengan Partisipasi Masyarakat Sebagai Moderating (Business and Accounting Education Journal, 2021)
The purpose of this study was to analyze the effect of the use of information technology, competence of local government apparatus, and internal control systems on the performance of government agencies with community participation as a moderating variable. The population of this research is Regional Apparatus Organizations in Kebumen Regency as many as 50 OPD and the sample used is 35 OPD, taken by cluster random sampling technique. The data analysis method used descriptive analysis and moderated regression analysis (MRA). The results showed: the use of information technology, competence of local government apparatus, and internal control systems simultaneously have a positive significant on the performance of government agencies with community participation as a moderating variable.